2019
DOI: 10.1108/afr-10-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Financing from Islamic microfinance institutions: evidence from Indonesia

Abstract: Purpose The purpose of this paper is to investigate factors that determine rural households’ access to finance provided by Islamic microfinance institutions (MFIs) in Indonesia. Design/methodology/approach A two-year panel data set with logistic regression is used to identify the determinants of access to finance by rural households. The study sample comprises of 289 Islamic MFIs’ clients and 140 non-clients from East Java, Indonesia. The clients consist of 111 rural households with profit and loss sharing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 15 publications
1
34
0
4
Order By: Relevance
“…After identifying the main motivations of taking credit, the focus is now on the sources from where funds are obtained and how individ- sources, notably from formal institutions at 7%, and from family/friends (4.3%) and saving clubs (2.8%) (see Table 7). Our findings are generally in line with those for Vietnam (Do et al, 2020;Khoi et al, 2013), and those of Fianto, Gan, and Hu (2019) for Islamic microfinance in Indonesia, although the latest found that males are more likely to borrow than females. Credit through Islamic financial services might be more widely available among men, although conventional informal finance is more often found to be larger among women in Indonesia (Esquivias et al, 2020).…”
Section: Examination Of Determinants Of Sources Of Financial Fundssupporting
confidence: 90%
“…After identifying the main motivations of taking credit, the focus is now on the sources from where funds are obtained and how individ- sources, notably from formal institutions at 7%, and from family/friends (4.3%) and saving clubs (2.8%) (see Table 7). Our findings are generally in line with those for Vietnam (Do et al, 2020;Khoi et al, 2013), and those of Fianto, Gan, and Hu (2019) for Islamic microfinance in Indonesia, although the latest found that males are more likely to borrow than females. Credit through Islamic financial services might be more widely available among men, although conventional informal finance is more often found to be larger among women in Indonesia (Esquivias et al, 2020).…”
Section: Examination Of Determinants Of Sources Of Financial Fundssupporting
confidence: 90%
“…The variable product knowledge does not have a significant effect. Fianto et al., 2019a , Fianto et al., 2019b prove that age and income significantly affect the decisions of rural communities in Indonesia in applying for LKMS financing. In addition, male respondents are more likely to access LKMS than women.…”
Section: Existing Researchmentioning
confidence: 97%
“…Socialization and education can prioritize men as the head of the family because of the above research. Men are more likely to access IMFI than women ( Fianto et al., 2019a , Fianto et al., 2019b ).…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia has the world's largest Muslim population and presents a broader market for Islamic financial products and services (Fianto et al, 2019a(Fianto et al, , 2019b. The Islamic Financial Services Board [IFSB] (2018) reports that Islamic banking in emerging countries including Indonesia is exhibiting significant improvements in profitability.…”
Section: Public Interest Statementmentioning
confidence: 99%